A study on aerobic power in wheelchair basketball athletes - Cai, A. F. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of the study was to test aerobic power in wheelchair basketball athletes with different training levels. Study findings will provide scientific data for the fitness of wheelchair basketball players and guide the development of training for disabled sports.